El sistema de los nmeros reales, la recta real - Cruzado Mantilla, Mario Agustin (2019)
The work of professional sufficiency is entitled The system of real numbers, the real line; whose development of the learning session is based on the consultation of bibliographic references and other sources of consultation as well as the application of knowledge acquired during the academic years of my professional training and according to my work experience of recent years, whose conclusions indicate that to increase the interest of the student and to know about the real numbers, it is necessary to help understand the situations that arise in everyday life._x000D_ The competence that is developed in this learning session corresponds to: Solve quantity problems, the didactic processes allow to better organize the learning processes of the students, organizing their knowledge in an orderly manner, promoting collaborative activity since it allows integrating in group to all the students, being the most advisable to work in team.